2020
DOI: 10.1007/s40820-020-0376-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Hybrid Biofuel and Triboelectric Nanogenerator for Bioenergy Harvesting

Abstract: • A triboelectric nanogenerator (TENG) and a glucose fuel cell (GFC) were separately designed to harvest biomechanical energy from body motion and biochemical energy from glucose molecules. • A hybrid energy-harvesting system (HEHS) which consisted of TENG and GFC was developed successfully, and it can simultaneously harvest biomechanical energy and biochemical energy. ABSTRACT Various types of energy exist everywhere around us, and these energies can be harvested from multiple sources to power micro-/nanoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…Moreover, the hybrid nanogenerator is demonstrated as a self-powered pressure sensor in bio-liquid, where the FBFC serves as the power source and PENG functions as the pressure sensor. Similarly, Li et al reported a hybrid biofuel and TENG on a larger scale as shown in Figure 6F (Li et al, 2020). The hybrid energy harvesting system (HEHS) incorporates a TENG and glucose fuel cell (GFC) on a flexible PET substrate for simultaneously ll OPEN ACCESS Figure 6.…”
Section: Ll Open Accessmentioning
confidence: 92%
“…Moreover, the hybrid nanogenerator is demonstrated as a self-powered pressure sensor in bio-liquid, where the FBFC serves as the power source and PENG functions as the pressure sensor. Similarly, Li et al reported a hybrid biofuel and TENG on a larger scale as shown in Figure 6F (Li et al, 2020). The hybrid energy harvesting system (HEHS) incorporates a TENG and glucose fuel cell (GFC) on a flexible PET substrate for simultaneously ll OPEN ACCESS Figure 6.…”
Section: Ll Open Accessmentioning
confidence: 92%
“…To ensure the two layers can separate after the pressing, i.e., the two friction layers, there should be a backbone made with highly resilient materials, such as titanium. Then, considering that there are also other layers used for friction, electrode, and encapsulation, the actual thin-film device will have a multi-layer structure, as shown in Figure 4 (B1) [ 62 ]. Another design is the “keel structure”, as shown in Figure 4 (B2).…”
Section: The Development Of Teng-based Self-powered Nerve Stimulatmentioning
confidence: 99%
“…Considering that the above-mentioned three designs share similar materials and encapsulation process, their open-circuit voltage, V oc , can be a fair comparison. The design combining spacer and keel structure has a V oc of 90 V [ 64 ], which is higher than that of spacer design, i.e., 20 V [ 62 ], and keel structure design, i.e., 60 V [ 63 ].…”
Section: The Development Of Teng-based Self-powered Nerve Stimulatmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated only such combination working in proof-of-concept in-vitro settings, hence are challenging to be employed for real-life scenarios. [37][38][39] Adapting the microgrid design concept, this work seamlessly integrates biomechanical and biochemical harvesters along with energy storage devices, with carefully budgeted energy rating, into one e-textile platform for the first time. When this microgrid harvests energy during human movements, the TEG storage modules are firstly activated from the instant motion-induced charge generation to harvest biomechanical energy to rapidly boot the system, while the subsequently activated BFCs harvest biochemical energy from enzymatic reactions of sweat metabolites for prolonged power delivery (Fig.…”
Section: Introductionmentioning
confidence: 99%